Association Between Health Workforce Availability and Management with the for Optimizing Stunting Prevention Services (Journal of Social And Education Research, 2024)
Stunting remains a significant public health challenge in Indonesia, particularly in Papua Province, where prevalence rates are high. Effective prevention at the primary health care level requires adequate availability and management of health human resources (HRH) to ensure optimal service delivery. This study aimed to examine the relationship between HRH availability and management and the optimization of stunting prevention services at Kosiwo Health Center, Yapen Islands Regency, Papua Province. An observational cross-sectional study was conducted, involving all 41 health workers engaged in stunting prevention using total sampling. Data were collected through a validated structured questionnaire and analyzed with SPSS, employing univariate and bivariate analyses, including the chi-square test at a significance level of ? = 0.05. The results indicated a significant relationship between HRH availability and management and the optimization of stunting prevention services. Health workers reporting adequate HRH management achieved higher rates of optimal service delivery (95.8%) compared to those with inadequate management (11.8%). These findings highlight that the proper availability and management of HRH are critical for enhancing stunting prevention programs. Strengthening HRH capacity, equitable distribution, and effective management are essential strategies to ensure the success of interventions aimed at reducing stunting in high-prevalence areas.